OVERVIEW ENGLISH ASA SECOND LANGUAGE FOR YOUNG LEARNERS - Rini, Setia (State Institute of Islamic Studies Salatiga, 2016)
Young learners have special charactheristics hence the teachers of English as a Second language needs special strategy too. It is indicated that the increas of abilities to learn second language is started from the early age. We can imagine when the teachers do not use and apply appropriate teaching methods and strategy in teaching English for young learners. As a result, the students? achievement does not work well. Thus, except to be successful in teaching English for young learners, it is very necessary for teachers to understand the characteristics of young learners.? Learning method s will influence how a teacher makes a lesson plan according to young learners? minds. This article tries to explain some methods of young learners in teaching English as a second language for young learners